A new kind of special function and its application - 范洪义 万志龙 吴泽 张鹏飞 (Chinese physics B, 2015)
By virtue of the operator Hermite polynomial method and the technique of integration within the ordered product of operators we derive a new kind of special function, which is closely related to one- and two-variable Hermite polynomials.Its application in deriving the normalization for some quantum optical states is presented.